LO35: Characterizing pain in children with acute gastroenteritis presenting to the emergency department. (May 2019) - Ali, S.; Maki, C.; Xie, J.; Lee, B.; Graham, T.; Vanderkooi, O.; MacDonald, S.; Poonai, N.; Thull-Freedman, J.; Rajagopal, M.; Dow, N.; Sivakumar, M.; et al.
Abstract : Introduction : Although acute gastroenteritis is an extremely common childhood illness, there is a paucity of literature characterizing the associated pain and its management. Our primary objective was to quantify the pain experienced by children with acute gastroenteritis in the 24-hours prior to emergency department (ED) presentation. Secondary objectives included describing maximum pain, analgesic use, discharge recommendations, and factors that influenced analgesic use in the ED.Methods : Study participants were recruited into this prospective cohort study by the Alberta Provincial Pediatric EnTeric Infection TEam between January 2014 and September 2017. This study was conducted at two Canadian pediatric EDs; the Alberta Children's Hospital (Calgary) and the Stollery Children's Hospital (Edmonton). Eligibility criteria included < 18 years of age, acute gastroenteritis (□ 3 episodes of diarrhea or vomiting in the previous 24 hours), and symptom duration □ 7 days. The primary study outcome, caregiver-reported maximum pain in the 24-hours prior to presentation, was assessed using the 11-point Verbal Numerical Rating Scale.Results : We recruited 2136 patients, median age 20.8 months (IQR 10.4, 47.4); 45.8% (979/2136) female. In the 24-hours prior to enrolment, 28.6% (610/2136) of caregivers reported that their child experienced moderate (4-6) and 46.2% (986/2136) severe (7-10) pain in the preceding 24-hours. During the emergency visit, 31.1% (664/2136) described pain as moderate and 26.7% (571/2136) as severe. In the ED, analgesia was provided to 21.2% (452/2131) of children. The most commonly administered analgesics in the ED were ibuprofen (68.1%, 308/452) and acetaminophen (43.4%, 196/452); at home, acetaminophen was most commonly administered (77.7%, 700/901), followed by ibuprofen (37.5%, 338/901). Factors associated with analgesia use in the ED were greater pain scores during the visit, having a primary-care physician, shorter illness duration, fewer diarrheal episodes, presence of fever and hospitalization.Conclusion : Although children presenting to the ED with acute gastroenteritis experience moderate to severe pain, both prior to and during their emergency visit, analgesic use is limited. Future research should focus on appropriate pain management through the development of effective and safe pain treatment plans.